Comparison of Immediate Versus Delayed Percutaneous Coronary Intervention on Recovery and Complications in Diabetic Patients with Acute ST Segment Elevation Myocardial Infarction: A Cross-Sectional Study: Immediate Versus Delayed PCI in Diabetic Patients with Acute ST-SEMI - Gul, Safa; Shakir, Shifa; Ullah, Motee; Usman, Hazrat; Ali, Babar; Awais, Muhammad (Pakistan Journal of Health Sciences, 2025)
Acute STEMI in diabetic patients leads to worse outcomes, making timely PCI crucial. However, the optimal timing (immediate vs. delayed) of percutaneous coronary intervention (PCI) for long-term recovery and complications in diabetic individuals is still being investigated. Objectives: To compare recovery and complication rates in diabetic acute STEMI patients undergoing immediate versus delayed PCI. Methods: This analytical cross-sectional study was conducted at a tertiary care hospital in Peshawar, Pakistan (October 2024 to March 2025), and enrolled 296 adult diabetic STEMI patients (aged ≥18 years) requiring PCI. After informed consent, data on demographics, medical history, procedural details, and post-PCI outcomes were collected via a structured questionnaire. Participants were categorized into immediate and delayed PCI groups, with statistical analysis using descriptive statistics and Chi-square tests to compare outcomes. Results: A total of 296 diabetic STEMI patients were enrolled, with 32.1% undergoing immediate PCI and 67.9% delayed PCI. The mean age was 55.89 ± 11.57 years, and 77% had type 2 diabetes. The delayed PCI group included a higher percentage of male; however, this variation was not significant. Baseline LVEF did not differ significantly (immediate: 40.54 ± 6.49 vs. delayed: 41.33 ± 7.23, p>0.05). Both groups showed significant post-PCI LVEF improvement (immediate: 49.12 ± 7.10, delayed: 50.85 ± 6.80), but the intergroup difference remained non-significant. No statistically significant differences were observed in intra- or post-procedural complications between the groups. Conclusions: In diabetic STEMI patients, a slight clinical delay in PCI did not significantly impact functional recovery (LVEF improvement) or increase intra- and post-procedural complications when compared to immediate intervention.